Perspectives of Vietnamese Students and Teachers on the Effectiveness of Grammarly in English Writing Development - Luu Thi Mai, Vy; Tran Vo Nhu , Quỳnh; Nguyen Minh, Hiếu; Tran Thi Hong, Nhung (English Education:Journal of English Teaching and Research, 2025)
This study seeks to investigate the efficacy of Grammarly, an AI-powered tool, in enhancing English writing skills from both teachers' and students' viewpoints. To achieve this, the study employed a qualitative case study approach, conducting semi-structured interviews with five teachers and ten students at a private university in Ho Chi Minh City, Vietnam. The data were analyzed through thematic analysis to uncover patterns and insights. The findings indicate a consensus among students and teachers regarding Grammarly's value in augmenting writing skills, particularly in its capacity for error detection and the provision of immediate feedback. However, notable differences in opinion emerged between the two groups. While students tend to unquestioningly embrace the feedback from Grammarly, teachers approach the tool’s suggestions with more critical evaluation. The distinction highlights differing attitudes towards the role of Grammarly in writing development and points to significant pedagogical implications for its integration into English language instruction.